Antimicrobial screening to molecular docking of newly synthesized ferrocenyl-substituted pyrazole - Shashi Sharma; Hardeep Singh Tuli; Mehmet Varol; Pallvi Aggarwal; Anita Rani; Abbas, Zahoor; Manoj Kumar (International Journal of Health Sciences, 2022)
Objective: Microbial diseases are snowballing at an alarming proportion. Therefore, the intent of this study was to inspect the antimicrobial action of ferrocenyl-substituted pyrazole against various human pathogenic Gram-positive, Gram-negative, and fungal microbial strains. Pyrazoles have been recognized for over a century as a significant and bioactive class of heterocyclic compounds. The association of pyrazoles with a ferrocene moiety may give new class of compounds. The present study was designed to synthesize biological active ferrocenyl-substituted pyrazole through a novel route. Methods: The anhydride of ferrocenyl-substituted pyrazole, namely, (S)-(3-(3-(carboxyamino)-3H-pyrazol-4-yl)cyclopenta-1,3-dien-1-yl)(cyclopenta-1,3-dien-1-yl)iron was synthesized using expansion cyclocondensation. FTIR, NMR, and GC-MS were performed to analyze the structure of the synthesized ferrocenyl-substituted pyrazole. Antimicrobial, DNA photo-cleaving, and anti-angiogenic activities of ferrocenyl-substituted compounds were studied. Results: Anhydride of (S)-(3-(3-(carboxyamino)-3H-pyrazol-4-yl)cyclopenta-1,3-dien-1-yl)(cyclopenta-1,3-dien-1-yl)iron obtained with yield of 87%. Spectral analysis confirmed the formation of anhydride. The synthesized compound was found to be biological active in the range of 85–95 μg/ml. Conclusion: This study described the novel method for the synthesis of biologically active anhydride of ferrocenyl-substituted pyrazole. The study demonstrations that synthesized ferrocenyl-substituted pyrazole in today’s situation is the encouraging antimicrobial mediator against the human pathogens. In addition, it may open new doors to initiate research against drug resistance bacteria with possible biomedical applications.